2021
DOI: 10.1186/s12889-021-11814-5
|View full text |Cite
|
Sign up to set email alerts
|

Population preferences and attitudes towards COVID-19 vaccination: a cross-sectional study from Pakistan

Abstract: Background While vaccine development is itself a challenge; ensuring optimal vaccine uptake at population level can present an even more significant challenge. Therefore, this study aimed to assess the Pakistani population’s attitude and preferences towards the Coronavirus disease 2019 (COVID-19) vaccine. Method A cross-sectional study was carried out through an online self-administered questionnaire from 27 September 2020 to 11 October 2020. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 44 publications
(64 reference statements)
6
55
4
Order By: Relevance
“…75 An earlier online study conducted during September-October 2020 with 883 respondents showed a similar acceptance rate of 70.8% for COVID-19 vaccination. 76 The acceptance rates were also close to those in the study by Solís Arce et al that used phone interviews in a sub-national sample (76.1% during July-September 2020, that declined to 66.5% during September-October 2020). 34 The acceptance rate for COVID-19 vaccination in Pakistan was also similar among healthcare workers in an online survey with 5237 respondents during December 2020-February 2021, which showed an acceptance rate of 70.2%.…”
Section: Pakistansupporting
confidence: 84%
“…75 An earlier online study conducted during September-October 2020 with 883 respondents showed a similar acceptance rate of 70.8% for COVID-19 vaccination. 76 The acceptance rates were also close to those in the study by Solís Arce et al that used phone interviews in a sub-national sample (76.1% during July-September 2020, that declined to 66.5% during September-October 2020). 34 The acceptance rate for COVID-19 vaccination in Pakistan was also similar among healthcare workers in an online survey with 5237 respondents during December 2020-February 2021, which showed an acceptance rate of 70.2%.…”
Section: Pakistansupporting
confidence: 84%
“…As with previous research, a lower proportion of vaccinated family members and close friends was associated with a lower probability of individuals' vaccination (p < 0.05) [18,[36][37][38][39][40]. A survey formed on the Health Belief Model was conducted in January 2021, indicating that perceived barriers and recommendations from friends or family were also associated with vaccination behavior directly and in combination, since family and friends may affect individuals' vaccination willingness or behavior through daily communication.…”
Section: Discussionmentioning
confidence: 54%
“…These were assessed based on a survey tool and guidance [21]. Some of the statements we used in this study were modified from previous studies on COVID-19 vaccination [22][23][24]. This section started with a question about whether the vaccines would produce an immune response against COVID-19.…”
Section: Study Design and Participantmentioning
confidence: 99%